Implementasi Pendekatan TPACK untuk Meningkatkan Motivasi dan Kemampuan Literasi Sains Peserta Didik Kelas VII SMP Negeri 27 Makassar - Marnia Marnia; Salma Samputri; Nurhayani H. Muhiddin (Celebes Science Education, 2026)
This study aims to determine: 1) the level of motivation and scientific literacy skills of seventh-grade students of SMP Negeri 27 Makassar before the implementation of learning using the TPACK approach. 2) The level of motivation and scientific literacy skills of seventh-grade students of SMP Negeri 27 Makassar after the implementation of learning using the TPACK approach. 3) Improvement in motivation and scientific literacy skills of seventh-grade students of SMP Negeri 27 Makassar after the implementation of learning using the TPACK approach. The type of research used in this study is Pre-Experimental research. The subjects of this study are seventh-grade students of SMP Negeri 27 Makassar. The results of the analysis concluded that: 1) The level of motivation and scientific literacy skills of students before the implementation of the TPACK approach, the learning motivation score is 48.16, which falls into the low category, and the pretest score for scientific literacy skills is 3.60, which falls into the less category. 2) The level of motivation and scientific literacy skills of students after the implementation of the TPACK approach, with a posttest score for learning motivation of 80.80, which falls into the high category, and a posttest score for scientific literacy skills of 7.28, which falls into the adequate category. 3) There is an improvement in students' scientific literacy skills after the implementation of the TPACK approach, with the N-Gain for motivation being 0.62 and the N-Gain for scientific literacy skills being 0.31, both falling into the moderate category. 4) There is a significant improvement in the motivation and scientific literacy skills of seventh-grade students of SMPN 27 Makassar after the implementation of learning using the TPACK approach.